2020
DOI: 10.1016/j.jaging.2020.100875
|View full text |Cite
|
Sign up to set email alerts
|

“Fiercely independent”: Experiences of aging in the right place of older women living alone with physical limitations

Abstract: This study explores the experience of aging among older Canadian women with physical limitations who live by themselves. While aging in place has been a policy priority in rapidly greying Canada, a lack of complementary public supports poses challenges for many older adults and their family members. Employing a qualitative methodology, and drawing from the notion of aging in the right place , we collected personal narratives of 12 women (aged 65 to 92) in two geographic areas in Ontario,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…Older adults may demonstrate a collective silence that will discourage housing modification behaviors from occurring. A study from Canada found that although older women have become less mobile with time and physical aging, they will largely maintain collective silence of their needs in terms of coping strategies and resources to change their living environment ( Narushima & Kawabata, 2020 ). On this occasion, they often overcome the environmental obstacles they face through their psychological adjustment ( van Kessel, 2013 ), and even very frail older adults are mentally resilient ( Peace et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults may demonstrate a collective silence that will discourage housing modification behaviors from occurring. A study from Canada found that although older women have become less mobile with time and physical aging, they will largely maintain collective silence of their needs in terms of coping strategies and resources to change their living environment ( Narushima & Kawabata, 2020 ). On this occasion, they often overcome the environmental obstacles they face through their psychological adjustment ( van Kessel, 2013 ), and even very frail older adults are mentally resilient ( Peace et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, when the perception and subjective norms are stronger, the attitude of older people toward home modifications is stronger. Studies have also found that older adults who are knowledgeable about the effects and costs of modifications have more positive attitudes and stronger behavioral intentions for modifications ( Narushima & Kawabata, 2020 ). The evidence leads us to propose the following hypotheses.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…preserve their personal beliefs, values and identities; and avoid being a burden and causing conflict by living in their own home without help from anyone (Narushima & Kawabata, 2020;Tan et al, 2015). Although it is not easy to live alone with disability and frailty, their independent lives are supported by available external resources and/or informal care.…”
Section: Discussionmentioning
confidence: 99%
“…Providers must consider the medical, psychosocial, and environmental resources available where their older patients reside in order to provide high-quality, appropriate, and supportive patient care. 1 5 An older adult residing in a long-term care nursing facility has both high daily care needs and access to on-site care resources (e.g., medication management, tracking of bowel and bladder function); thus, their health care teams should construct a care plan inclusive of those needs and resources. 6 On the other hand, a team may incorrectly assume that a patient residing within a senior apartment community has some of the same resources, resulting in an impractical and unsafe care plan.…”
Section: Introductionmentioning
confidence: 99%